Uralsk municipal solid waste disposal - Bulekova, А. А.; Murzashev, T. K.; Gubasheva, B. E.; Gabdullina, S. M. (My University, 2021)
Currently, there is an increase in household waste due to the large population growth. To effectively manage the generation of solid domestic waste, it is necessary to know the rate of waste generation and their composition. According to these parameters, the test site of the city of Uralsk was investigated. The study proposed alternative solutions to the problem of solid waste disposal using new technologies.В настоящее время наблюдается рост бытовых отходов из-за большого прироста населения. Чтобы эффективно управлять образованием твердых бытовых отходов, необходимо знать скорость образования отходов и их состав. По этим параметрам исследован полигон города Уральска. В исследовании предложены альтернативные решения проблемы утилизации твердых бытовых отходов с использованием новых технологий.
International Scientific and Practical Conference on Ensuring Sustainable Development in the Context of Agriculture, Green Energy, Ecology and Earth Science, ESDCA 2021
Keywords: импакт-фактор 2021; зарубежное издание; конференции; скопус; бытовые отходы; охрана окружающей среды; утилизация твердых отходов; scopus